Syngas Underground Coal Gasification (UCG) Testing of Fracture Type Subbituminous Coal in Laboratory Scale: Underground Coal Gasification (UCG) - Joniken Lesmana; Abu Hasan; Aida Syarief (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Underground Coal Gasification is a method used to convert underground coal seams into a gaseous product commonly called synthetic gas through a flammable chemical process without going through a conventional mining process. The UCG concept was first developed in England which was then continued by the Soviet Union in field trials of UCG which was used as a power plant. In Indonesia, Tekmira has begun to research UCG, but there are very few publications on UCG. Therefore, it is necessary to conduct research on laboratory scale UCG for analysis of gas products to support the study of renewable energy. UCG testing begins with sample preparation followed by laboratory-scale coal gasification testing. There is a sample of coal used in the test, namely Subbituminous Coal from Tanjung Enim, South Sumatra. Initial combustion is carried out by flowing propane gas into the reactor tube using a burner. Furthermore, a mixture of oxygen gas and compressed air is used to keep the coals burning. After obtaining the gas from the combustion, then gas sampling is carried out using a suction pump which will be stored in a tedlar gas bag. Combustion gas products will be checked for syngas concentration using a Gas Chromatography tool to determine the concentration of CH4, CO2 and O2 gases. From the tests that have been carried out, the gas concentrations of O2 are 3.67%, CO2 41.51%, and CH4 6.93%. Coal in the confined test conditions has good conditions with indications of seeing the concentration of CH4, O2, and CO2 gas.